Pediatric Tularemia—A Case Series From a Single Center in Switzerland. (11th June 2022) - Schöbi, Nina; Agyeman, Philipp K A; Duppenthaler, Andrea; Bartenstein, Andreas; Keller, Peter M; Suter-Riniker, Franziska; Schmidt, Kristina M; Kopp, Matthias V; Aebi, Christoph
Abstract: Background: The incidence of tularemia has recently increased throughout Europe. Pediatric tularemia typically presents with ulceroglandular or glandular disease and requires antimicrobial therapy not used in the empirical management of childhood acute lymphadenitis. We describe the clinical presentation and course in a case series comprising 20 patients. Methods: This is a retrospective analysis of a single-center case series of microbiologically confirmed tularemia in patients <16 years of age diagnosed between 2010 and 2021. Results: Nineteen patients (95%) presented with ulceroglandular (n = 14) or glandular disease (n = 5), respectively. A characteristic entry site lesion (eschar) was present in 14 (74%). Fever was present at illness onset in 15 patients (75%) and disappeared in all patients before targeted therapy was initiated. The diagnosis was confirmed by serology in 18 patients (90%). While immunochromatography was positive as early as on day 7, a microagglutination test titer 1:≥160 was found no earlier than on day 13. Sixteen patients (80%) were initially treated with an antimicrobial agent ineffective against F. tularensis . The median delay (range) from illness onset to initiation of targeted therapy was 12 (6–40) days. Surgical incision and drainage were ultimately performed in 12 patients (60%). Conclusions: Pediatric tularemia in Switzerland usually presents with early, self-limiting fever and a characteristic entry site lesion with regional lymphadenopathy draining the scalp or legs. Particularly in association with a tick exposure history, this presentation may allow early first-line therapy with an agent specifically targeting F. tularensis, potentially obviating the need for surgical therapy.